Scientometric Analysis of Medicinal and Edible Plant Coptis - Huang, Zhibang; Hou, Zhengkun; Liu, Fengbin; Zhang, Mei; Hu, Wen; Xu, Shaofen (Frontiers in Pharmacology, 2021)
Objective: A scientometric analysis to obtain knowledge mapping of Coptis revealed the current research situation, knowledge base and research hotspots in Coptis research. Methods: Coptis-related documents published from 1987 to 2020 were selected through the Web of Science Core Collection. CiteSpace, VOSviewer and Microsoft Excel were used to construct knowledge maps of the Coptis research field. Results: A total of 367 documents and their references were analyzed. These papers were primarily published in mainland China (214), followed by Japan (57) and South Korea (52), and they each formed respective cooperation networks. The document co-citation analysis suggested that the identification of Coptis Salisb. species, the production of alkaloids, and the mechanisms of action of these alkaloids formed the knowledge bases in this field. A keyword analysis further revealed that the research hotspots were primarily concentrated in three fields of research involving berberine, Coptis chinensis Franch, and Coptis japonica (Thunb.) Makino. Oxidative stress, rat plasma (for the determination of plasma alkaloid contents), and Alzheimer’s disease are recent research hotspots associated with Coptis. Conclusion: Coptis research was mainly distributed in three countries: China, Japan, and South Korea. Researchers were concerned with the identification of Coptis species, the production of Coptis alkaloids, and the efficacy and pharmacological mechanism of the constituent alkaloids. In addition, the anti-oxidative stress, pharmacokinetics, and Alzheimer’s disease treatment of Coptis are new hotspots in this field. This study provides a reference for Coptis researchers.